Reflections on didactics of mathematics, citizenship education in the information age and educational reform in Latin America and paintings in their steps fractals (2019)
ABSTRACT: The intention of the present paper is to show that people have a series of educational needs in the era of information, so that they can become competent digital citizens. These educational needs are evident in the policies promoted by the United Nations Educational, Scientific and Cultural Organisation, which were well known to Latin American governments of the decades from the 1960s to the 1990s. Therefore, it is to be hoped that the educational reforms of 1990s have elements based on the principles of education that they advanced, which emphasises the preparation of subjects in the digital era, based on advances in information and communication technology, focusing on the teaching and learning of computer science.